Training and Implementation of Catfish Feed Technology in the Sedana Sari Fish Farmers Group in Selat Village, Abiansemal, Badung, Bali - Sang Ayu Made Putri Suryani; Anak Agung Sagung Putri Risa Andriani; I Gusti Ayu Dewi Seri Rejeki; Gede Agus Surya Pratama (Asian Journal of Community Services, 2023)
Catfish is one type of freshwater cultured fish that has the potential to be developed. Cultivation with advanced technology in intensive systems requires more feed intake good quality pellet feed is needed but at an affordable price. The problem of the high cost of cultivating catfish is a challenge that must be resolved. Activities were carried out in 3 stages including counseling and workshops, planning, the practice of making fish feed pellets, and monitoring and evaluating. The results in the activities of catfish farmers conveyed problems and exchanged experiences of the problems experienced. Furthermore, to find out the sustainability of the program, the team conducted monitoring and evaluation and the activities continued even though there were few problems.